The Effect of Production Process and Product Innovation on Product Quality (Survey on Convection Sinar Bintang Pangandaran) - Tanti Tiara; Suci Putri Lestari; Barin Barlian (Journal of Indonesian Management, 2022)
This study aimed to determine the effect simultaneous and partial of the production process and product innovation on product quality in Convection Sinar Bintang Pangandaran. The method used in the this research is a causal method with a quantitative approach. The research data were obtained by distributing questioners to Convection Sinar Bintang employees.The data collected consist of primary data and secondary data. Data analysis in this study used multiple regression analysis using SPSS software.The results of this study indicade that the production process and product innovation simultaneously had a significant positive effect on product quality in the Convection Sinar Bintang Pangandaran. Partially, production process has a significant positife effect on product quality in the Convection Sinar Bintang Pangandaran. Partially, product innovation has a significant positife effect on product quality in the Convection Sinar Bintang Pangandaran.